Antibacterial Activity of AXOTL-13, a Novel Peptide Identified from the Transcriptome of the Salamander Ambystoma mexicanum - Laura Córdoba; Daniela López; Mariana Mejía; Fanny Guzmán; Dina Beltrán; Belfran Carbonell; Laura Medina (Pharmaceutics, 2024)
Background/Objectives: Antimicrobial peptides are essential molecules in the innate immunity of various organisms and possess a broad spectrum of antimicrobial, antitumor, and immunomodulatory activities. Due to their multifunctionality, they are seen as an alternative for controlling bacterial infections. Although conventional antibiotics have improved health worldwide, their indiscriminate use has led to the emergence of resistant microorganisms. To discover new molecules with antimicrobial activity that could overcome the limitations of traditional antibiotics, this study aimed to identify antimicrobial peptides in Ambystoma mexicanum. Methods: In this study, hypothetical proteins encoded in the Ambystoma mexicanum transcriptome were predicted. These proteins were aligned with peptides reported in the Antimicrobial Peptide Database (APD3) using the Fasta36 program. After identifying peptide sequences with potential antibacterial activity, their expression was confirmed through conventional polymerase chain reaction (PCR) and then chemically synthesized. The antibacterial activity of the synthesized peptides was evaluated against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. Results: A new antimicrobial peptide named AXOTL-13 was identified. AXOTL-13 is an amphipathic cationic alpha-helical peptide with the ability to inhibit the growth of Escherichia coli without causing hemolysis in red blood cells, with its action likely directed at the membrane, as suggested by morphological changes observed through scanning electron microscopy. Conclusions: This research is pioneering in evaluating the activity of antimicrobial peptides present in Ambystoma mexicanum and in specifically identifying one of these peptides. The findings will serve as a reference for future research in this field.